USER AUTHENTICATION SECURITY - Lastovskis, Andris; Grabusts, Pēteris (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2017)
Nowadays, the rapid development of technology and increased amount of data that must be processed and stored. All stakeholders are interested in security level of their system. To improve security, specific process was created, which will help identify the user, and only then give him access. As a result, developed process – authentication, it’s purpose of this is to improve user identification process, and to let him go further. In the end, as a result, this process either allows the user to work with the system, or rejects it because incorrect data was received by system. Often, the authentication process is based on some secret element that both the system and the user himself knows about. As an example it can be system’s provided login and password, some readable element, or even fingerprints.